EMPOWERMENT STRATEGY OF MANEKAT 1 FARMER GROUP THROUGH CROP ROTATION PATTERN IN SUSTAINABLE AGRICULTURAL SYSTEM IN EAST PENFUI VILLAGE, CENTRAL KUPANG SUB-DISTRICT, KUPANG REGENCY - Dalu, Fransiska Opinsia; Kapioru, Charles; Un, Paulus (Undana Press, 2025)
This research was conducted in the Manekat 1 farmer group from October to November 2024, the objectives of this study were 1) To deter mine the empowerment strategy used in empowering members of the Manekat 1 farmer group. 2) To determine the benefits obtained by farmers from crop rotation carried out in the Manekat 1 farmer group. The number of samples in this study was 55 respondents. The research method used in this study is a descriptive method with a mix method approach. Data collection methods with observation and interviews, questionnaires, documentation and literature studies. The data analysis method uses SWOT analysis by identifying internal factors (IFAS) and identifying external factors (EFAS) and using cost and income analysis methods. The results of the SWOT analysis show that an aggressive strategy where this strategy brings together strength and opportunities so the empowerment strategy of the Manekat 1 farmer group is an aggressive strategy whose strengths are in quadrant I.